Does anemia–polycythemia complicating twin–twin transfusion syndrome affect outcome after fetoscopic laser surgery?. (4th March 2016) - Donepudi, R.; Papanna, R.; Snowise, S.; Johnson, A.; Bebbington, M.; Moise, K. J.
Abstract: Objective: Twin anemia–polycythemia sequence (TAPS) can occur as a unique disease or as a complication of twin–twin transfusion syndrome (TTTS). Middle cerebral artery (MCA) Doppler studies are not currently part of the routine evaluation of monochorionic twins since they are not used in the Quintero staging system. As such, the true incidence of TAPS is unknown. We aimed to compare the characteristics and outcomes of twin pregnancies with TTTS complicated by spontaneous anemia–polycythemia vs those with TTTS alone. Methods: This was a secondary analysis of data collected prospectively from a cohort of 156 consecutive patients undergoing fetoscopic laser surgery for TTTS, between October 2011 and August 2014. TAPS was defined as discordance in the preoperative MCA peak systolic velocity (PSV), with one twin fetus having MCA‐PSV ≤ 1.0 multiples of the median (MoM) and the other having MCA‐PSV ≥ 1.5 MoM. Maternal demographics as well as preoperative, operative and postoperative variables were analyzed. Results: Included in the final analysis were 133 patients with complete records: 11 cases with TTTS with anemia–polycythemia and 122 cases with TTTS alone. There was no difference in maternal body mass index, gestational age (GA) at procedure, rate of preterm prelabor rupture of membranes or GA at delivery between the two groups. Patients with TTTS and anemia–polycythemia were more likely to be older ( P  = 0.03) and parous ( P  = 0.04) and had a significantly lower number of placental anastomoses ( P  = 0.01). The dual live‐birth rate was similar for both groups ( P  = 0.76). Conclusion: Cases of TTTS with anemia–polycythemia were more likely to be found in parous and older women and were characterized by fewer vascular anastomoses. TTTS with anemia–polycythemia was not associated with worse perinatal outcome after laser therapy. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.